PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Koto, Yola Ramadhona (Jurnal Edukasi dan Penelitian Matematika, 2023)
understanding the concept is a very important ability in the mathematics learning process that is expected to be mastered well by learners. The reality in field found that the understanding of the concept of mathematics among the class VIII students of SMPN 43 Padang for the 2022/2023 academic year was still low. One effort that can be made to improve students’ understanding of mathematical concepts is to apply models such as Think Talk Write learning. The purpose of this research is to describe whether the understanding of the mathematical concept of students who learn using the Think Talk Write learning model is better than the understanding of the mathematical concepts of students who learn by using the direct learning model in class VIII SMPN 43 Padang. This tipe of research in the class VIII at SMPN 43 Padang. Sample selection was done by random sampling technique. Class VIII-1 was selected as the experimental class and class VIII-3 as the control class. The instrument used is an understanding test of mathematical concepts in the form of description questions. Keywords — Mathematics Concepts Chomprehension, Think Talk Write, Direct Learning.